UPAYA PAKSA (DWANG MIDDELEN) DALAM DUGAAN TERJADINYA TINDAK PIDANA BAGI PENYIDIK - Bagus Teguh Santoso (Mimbar Yustitia: Jurnal Hukum dan Hak Asasi Manusia)
The supreme court didn’t make the gradation on the evidence law in the process of the law enforcement on the first stage/pre-trial (investigation and introgation) and the second stage/trial (prosecution and verdict). Meanwhile, the provisions of article 184 KUHAP is related with the provisions of the next article 185, 186, 187, 188, and 189 KUHAP. That proves that the gradation of legal evidence in article 184 is for the second stage/ trial process. The research method used in this research is normative legal research. The research approach used is the statutory approach, the conceptual approach and the cases approach to coercive measures (dwang middelen) in the alleged occurrence of criminal acts for investigators based on the Criminal Procedure Code and the Constitutional Court Decision Number: 21/ PUU-XII/2014. This study aims to analyze disharmony as a legal consequence of the Constitutional Court Decision No. 21/PUU-XII/2014.